1993
DOI: 10.1080/02699939308409184
|View full text |Cite
|
Sign up to set email alerts
|

Emotional influences on semantic priming

Abstract: Influences of mood on qualitative aspects of cognitive processing are examined within a semantic priming paradigm. The priming effect reflects the reduction of latency for a lexical decision task when a target word is presented in combination with an associatively related prime word. The effect was higher for subjects in whom positive affect had been induced than for a control group, if prime and target were high-associatively related. There was no effect of mood on priming for low-associatively related prime-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0
21

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 20 publications
5
47
0
21
Order By: Relevance
“…We argue that this phasic affective modulation took place because the sounds worked as brief affect inductions, with positive compared to negative affect increasing the extent to which semantic activation propagated from a prime to related concepts, such as in tonic affective modulation of semantic spread (e.g., Ashby et al, 1999;Hänze & Hesse, 1993;Storbeck & Clore, 2005). Because particularly indirect priming depends on remote semantic spread (Balota & Lorch, 1986;Baumann & Kuhl, 2002), positive compared to negative brief affect particularly increased the amount of indirect priming.…”
Section: Discussionmentioning
confidence: 96%
“…We argue that this phasic affective modulation took place because the sounds worked as brief affect inductions, with positive compared to negative affect increasing the extent to which semantic activation propagated from a prime to related concepts, such as in tonic affective modulation of semantic spread (e.g., Ashby et al, 1999;Hänze & Hesse, 1993;Storbeck & Clore, 2005). Because particularly indirect priming depends on remote semantic spread (Balota & Lorch, 1986;Baumann & Kuhl, 2002), positive compared to negative brief affect particularly increased the amount of indirect priming.…”
Section: Discussionmentioning
confidence: 96%
“…Thereby, it was proposed that the influence of emotional nodes is restricted to the retrieval of episodic memory events [Macleod, 1987]. Nevertheless, other studies revealed that there were facilitative effects of mood induction on lexical decisions [Haenze and Hesse, 1993;Hesse and Spies, 1996], weaker or no effects of affective information in comparison to semantic informatzion [Kemp-Wheeler and Hill, 1992;Matthews and Southall, 1991;Siegle et al, 2002], greater priming effects for negative emotional information [Matthews et al, 1995;Windmann et al, 2002], or greater effect for positive emotional information [Rossell et al, 2000]. To conclude, the existing behavioral studies revealed heterogeneous results but they also showed that emotional valence does have a specific influence on semantic processing.…”
Section: Introductionmentioning
confidence: 99%
“…(1998: 432) The central idea is that consciousness is an "anticipation" of a possible input. This point is illustrated by the experience of subjects in perceptual experiments who are instructed to imagine an object prior to its appearance on a screen, or to continue looking for the object while other objects are being flashed intermittently: consistently, the result is that the subjects perceive the object more readily when they are looking for it (Corbetta et al, 1990;Pardo et al, 1990;Logan, 1980;Hanze and Hesse, 1993;Legrenzi et al, 1993;Rhodes and Tremewan, 1993;Lavy and van den Hout, 1994). To imagine an object is to be "on the lookout" for it.…”
Section: The Anomaly Of Physicalistic Underexplanation: Chalmers' "Hamentioning
confidence: 97%